1992
DOI: 10.1128/jvi.66.3.1528-1534.1992
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between the fusion protein and hemagglutinin-neuraminidase of human parainfluenza viruses

Abstract: The fusion glycoprotein (F) and hemagglutinin-neuraminidase (HN) genes of human parainfluenza virus type 2 (P12) were molecularly cloned and expressed in HeLa-T4 cells by using the vaccinia virus-T7 transient expression system. Expression of the F and HN proteins was detected by using immunoprecipitation and surface inmunofluorescence staining. Although the F protein was found to be cleaved into F1 and F2 and expressed on cell surfaces, no cell fusion was observed. However, cotransfection of the F-protein gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(74 citation statements)
references
References 31 publications
8
66
0
Order By: Relevance
“…In most paramyxoviruses, the homotypic F and HN glycoproteins have been known to be physically associated with each other on the cell surface, indicating the attachment proteindependent mode of fusion (13,57). We found that the substitution of NDV F protein alone into rAPMV-2 conferred the ability to replicate in the brains of 1-day-old chicks when infected via the intracerebral route, indicative of neurotropism, or via the intranasal route, indicative of neuroinvasiveness.…”
Section: Discussionmentioning
confidence: 75%
“…In most paramyxoviruses, the homotypic F and HN glycoproteins have been known to be physically associated with each other on the cell surface, indicating the attachment proteindependent mode of fusion (13,57). We found that the substitution of NDV F protein alone into rAPMV-2 conferred the ability to replicate in the brains of 1-day-old chicks when infected via the intracerebral route, indicative of neurotropism, or via the intranasal route, indicative of neuroinvasiveness.…”
Section: Discussionmentioning
confidence: 75%
“…It has become increasingly clear that there is a difference in the requirements for fusion among different paramyxoviruses (Bagai and Lamb, 1995b;. Whereas most of the paramyxoviruses require the coexpression of homotypic F and HN proteins in order to induce cell-cell fusion (Ebata et al, 1991;Hu et al, 1992;Morrison et al, 1991;Sergel et al, 1993;Tanabayashi et al, 1992;Wild et al, 1991), a homotypic HN protein is not essential for SV5 F protein-mediated cell fusion (Bagai and Lamb, 1995b). Further evidence for the sufficiency of SV5 F protein in cell fusion comes from the finding that F mutants containing single Gly to Ala changes in the fusion peptide cause a remarkable increase in the syncytia formation compared to the wild-type (wt) F protein Ward et al, 1995).…”
mentioning
confidence: 99%
“…Based on this observation, we next wanted to establish what role, if any, the viral fusion protein played in trans-synaptic transport. While it is generally believed that H and F have interaction domains that coordinate receptor binding and fusion (Hu, Ray, and Compans, 1992), work by other laboratories has suggested that F may act independently of H, and may even govern target cell specificity. For example, in simian virus 5 (SV5), F promotes fusion in the absence of the hemagglutinin-neuraminidase (HN) protein, albeit less efficiently than when HN is present (Horvath et al, 1992;Ito et al, 1997).…”
Section: Introductionmentioning
confidence: 99%